Towards a perspective of everyday urbanism in researching migrants in urban China. (January 2022) - Qian, Junxi
Abstract: This paper presents one of the first theoretical interventions that apply a perspective of everyday urbanism to the research of (internal) migrants in reform-era urban China. Theoretically, the paper draws on two approaches that theorise the multifaceted relationships between everyday life and capitalist urbanization. The first, informed by Lefebvre's works, stresses the alienation of everyday life and the rationalisation of urban spaces, while asserting that everyday life contains the seeds of resistance to the colonising logics of capitalism. In the second approach, everyday urban practices are analysed in terms of a transversal logic to the state regime and the formal economy, or as the provisional intersections of heterogeneous social and material conditions that generate contingent outcomes and possibilities. Based on these theoretical premises, the paper develops a reinterpretation of existing literatures on migrants in China to see how a perspective of everyday urbanism enables us to rethink this field. The paper concludes by proposing everyday urbanism as a new frontier for research, and several ways in which future works can enrich our understandings of migrant lives, spaces and communities by engaging with this perspective. Highlights: This paper advocates an everyday urbanism perspective for studying migrants in China. It develops this perspective by engaging with two theoretical approaches. The first approach is informed by Lefebvre's critique of everyday life. The second is interested in transversality and urban life as provisional intersections. It develops a re-interpretation of extant studies on migrants in China based on this perspective.